2019
DOI: 10.1007/s13202-019-0736-4
|View full text |Cite
|
Sign up to set email alerts
|

Flow units and rock type for reservoir characterization in carbonate reservoir: case study, south of Iraq

Abstract: The current work is focused on the rock typing and flow unit classification for reservoir characterization in carbonate reservoir, a Yamama Reservoir in south of Iraq (Ratawi Field) has been selected, and the study is depending on the logs and cores data from five wells which penetrate Yamama formation. Yamama Reservoir was divided into twenty flow units and rock types, depending on the Microfacies and Electrofacies Character, the well logs pattern, Porosity-Water saturation relationship, flow zone indicator (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This revealed that geological conditions corresponded to each other [16], [17]. The equation is simplified if permeability and porosity are measured in millidarcy and fraction, respectively [18].…”
Section: Flow Zone Indicatormentioning
confidence: 76%
“…This revealed that geological conditions corresponded to each other [16], [17]. The equation is simplified if permeability and porosity are measured in millidarcy and fraction, respectively [18].…”
Section: Flow Zone Indicatormentioning
confidence: 76%
“…Figure (6) shows histograms and cross-plots for the Rumaila Formation groups between the wells used as generated by a k-means cluster analysis. Researchers in [20] were built four rock types and groups which are identified in the Yamama formation depending on the FZI method but in the current study, four rock types were defined and distributed vertically and horizontally among the 10 wells examined depending on Cluster Analysis Technique as shown in Figures (8) and (9).Each rock type is characterized by response of porosity and shale volume as well as microfacies type: The units of Rumaila Formation are characterized by the following:…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that the Yamama Formation is acting as a series of source-reservoir units in the petroleum system of southern Iraq, indeed, it forms a series of highly productive carbonate reservoirs in many of the super-giant oil fields in southern Iraq (e.g. Sadooni 1993; Aqrawi et al 2010; Abeed et al 2011; Al-Jawad & Saleh 2020).…”
Section: Geologic Setting and Lithostratigraphymentioning
confidence: 99%
“…The Lower Cretaceous Yamama Formation is one of the main carbonate reservoirs as well as good source rocks in southern Iraq and is equivalent to the Minagish Formation in Kuwait (Aqrawi et al 2010; Al-Khafaji et al 2022). Its facies change both laterally and vertically and it, therefore, acts as a source rock in some locations in southern Iraq, but not in others (Abeed et al 2011; Al-Jawad & Saleh 2020). This study is based on the palynological examination of five subsurface core samples (Table 1) from the Yamama Formation from boreholes R-167, Ru-158, Su-08, and Zb-42 in southern Iraq (Fig.…”
Section: Introductionmentioning
confidence: 99%